2022
DOI: 10.1002/aoc.6628
|View full text |Cite
|
Sign up to set email alerts
|

Characterization, theoretical computation, DNA‐binding, molecular docking, antibacterial, and antioxidant activities of new metal complexes of (E)‐1‐([1H‐1,2,4‐triazol‐3‐yl]diazenyl)naphthalen‐2‐ol

Abstract: Complexes of (E)-1- ([1H-1,2,4-triazol-3-yl]diazenyl)naphthalen-2-ol with manganese (II), cobalt (II), nickel (II), and zinc (II) have been constructed. Elemental analyses, molar conductance, magnetic moment measurements, spectral (IR, 1 H, 13 C NMR, EI-mass, and UV-Vis), XRD, and thermal studies have all been used to determine the structure of complexes. Except for Ni (II), which has a tetrahedral geometry, the results demonstrated that all complexes have octahedral geometry. The molecular mechanic calculatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 102 publications
(139 reference statements)
0
3
0
Order By: Relevance
“…Various strains of G(+ve) bacteria (S. aureus, B. cereus) and G(Àve) bacteria (P. aeruginosa, E. coli), were screened for susceptibility to the studied compounds utilizing agar diffusion study. 23,24 Petri plates have been protected with test microorganisms and soaked in nutrient agar media. The studied compounds were cut into uniform cubes (5.0 mm in diameter) through a final dose of 100 g.mL À1 and then emerged at 37 C for 24 h. We calculated the size of the observed inhibition zone to obtain a sense of the anti-bacterial behaviour.…”
Section: Antimicrobial Studiesmentioning
confidence: 99%
“…Various strains of G(+ve) bacteria (S. aureus, B. cereus) and G(Àve) bacteria (P. aeruginosa, E. coli), were screened for susceptibility to the studied compounds utilizing agar diffusion study. 23,24 Petri plates have been protected with test microorganisms and soaked in nutrient agar media. The studied compounds were cut into uniform cubes (5.0 mm in diameter) through a final dose of 100 g.mL À1 and then emerged at 37 C for 24 h. We calculated the size of the observed inhibition zone to obtain a sense of the anti-bacterial behaviour.…”
Section: Antimicrobial Studiesmentioning
confidence: 99%
“…Separately to the ability to proliferate, 1,2,4-triazole derivatives are able to have a cytoprotective effect. Cytoprotection is manifested in antioxidant [41][42][43][44][45], antihypoxic [46][47][48][49][50], hepatoprotective [51][52][53][54][55], neuroprotective [56][57][58][59][60] action. In particular, scientists [60] conducted an extensive review of 64 compounds that can find their application in the treatment of Alzheimer's disease.…”
Section: Cytoprotective Activity Of 124-triazolesmentioning
confidence: 99%
“…7). In the analyzed works [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60], 40 potential antioxidants were identified, among which the authors separately Note 4 molecules; 44 compounds with antihypoxic activity were identified, of which 5 are recommended for further study. 106 potential neuroprotectors were identified, of which 7 attract special attention of scientists.…”
Section: Cytoprotective Activity Of 124-triazolesmentioning
confidence: 99%